Media Pohon Pintar dalam Pembelajaran Kooperatif untuk Menstimulasi Sikap Ilmiah Siswa (UPEJ Unnes Physics Education Journal, 2019)
The low of scientific attitude and the usage of lecture method are the primary issues. This study employs cooperative multimodels method with Smart Tree on the topic of global warming to overcome the problems. This study aims to know the improvement of student’s scientific attitude, description of scientific attitude improvement, and to know the response of student’s attitude toward cooperative multimodels with Smart Tree. Samples for this study are students of VIIA & B SMPN 12 Semarang. Based on the result of the study, can be obtained that N-Gain from experiment class is 0.58 categorized as medium, while for control class is 0.3 categorized as low. From the result can be concluded that the improvement of student’s scientific attitude in experiment class which uses cooperative multimodels with Smart Tree is higher than that of control class which uses discussion and demonstration as the learning models. The scientific attitude improvement being analysed include 5 indicators: want to know attitude, honesty, communicative, cooperation, and responsibility. The student’s response to the learning with cooperative multimodels with Smart Tree is categorized as good with percentage 79%.